Faktor-Faktor Yang Berhubungan Dengan Pemeriksaan Inspeksi Visual Asetat Pada Wanita Usia Subur - M Kailani, Fitriani; Rohaya, Rohaya; Pastuty, Rosyati; Suprida, Suprida; Edyansyah, Erwin (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: Cervical cancer is a leading cause of cancer-related deaths among women in Indonesia. Visual Inspection with Acetic Acid (VIA) is an effective, affordable, and simple screening method. However, VIA coverage remains low, including in Toman Baru Village, Babat Toman Subdistrict, where only 17.6% of women of reproductive age (WRA) have undergone VIA screening. The purpose of this research is to identify the factors associated with VIA screening among WRA in Toman Baru Village. Methods: This is a quantitative study with a cross-sectional design. The population consisted of 245 WRA, and a sample of 152 participants was selected using proportional stratified random sampling. Data were collected using questionnaires and analyzed with the chi-square test. Results: Univariate analysis showed that 33.6% of WRA had undergone VIA screening. The majority of respondents were under 40 years old (63,2%), had 1–3 children (87,,5%), had low education (91,4%), were employed (52%), and had low knowledge (69.1%). Bivariate analysis showed significant associations between VIA screening and age (p=0,001), parity (p=0,005), education (p=0,034), occupation (p=0,001), and knowledge (p=0,001). Conclusion: Individual factors such as younger age, lower parity, higher education level, employment status, and good knowledge were significantly associated with VIA screening uptake.